2016
DOI: 10.3390/ijerph13111137
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Response in the Immediate Aftermath of Shaking: Earthquakes in Christchurch and Wellington, New Zealand, and Hitachi, Japan

Abstract: This study examines people's response actions in the first 30 min after shaking stopped following earthquakes in Christchurch and Wellington, New Zealand, and Hitachi, Japan. Data collected from 257 respondents in Christchurch, 332 respondents in Hitachi, and 204 respondents in Wellington revealed notable similarities in some response actions immediately after the shaking stopped. In all four events, people were most likely to contact family members and seek additional information about the situation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Within those 69% evaluated respondents, only 11% evacuated because of the environmental cue. There are similar patterns as well as significant differences between tsunami threats in relation to household reactions (16,18). More empirical evidence is needed to illustrate the impact variables on the evacuation decision and evacuation process (18).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Within those 69% evaluated respondents, only 11% evacuated because of the environmental cue. There are similar patterns as well as significant differences between tsunami threats in relation to household reactions (16,18). More empirical evidence is needed to illustrate the impact variables on the evacuation decision and evacuation process (18).…”
Section: Literature Reviewmentioning
confidence: 87%
“…4 in their paper). Moreover, Jon et al concluded that, the higher people's perceived shaking intensity and risk perceptions were, the less likely they were to resume their previous activities [39]. In addition, a comparison of the three teams of seismic intensity scales, JMA (Japan), MSK (Russia) and CSIS (China), indicated that the reaction of a person's feelings according to JMA is similar to that of CSIS [40].…”
Section:  =mentioning
confidence: 99%
“…Disaster experience shapes the individual's expectations of the future disasters and their behaviour [45]. Experience with disasters can motivate people to behave actively and take preventive (protective) measures [46], [47]. At the same time, it affects the subjective perception of one's own preparedness [48].…”
Section: Risk and Disaster Preparednessmentioning
confidence: 99%